How Democracy could foster Economic Growth: The Last 200 Years - Carol S. Leonard; Konstantin E\.. Yanovskiy; D. Shestakov (Gaidar Institute for Economic Policy, 2014)
In this paper we explore current understandings of the influence of political rights, among historical legacies, on economic development. We construct variables for selected political regimes for 1811-2010. We find significant association between individual rights and economic growth. We argue that current understanding of political regimes supportive of growth (Acemoglu, etc), should parse the concept of property rights to include the protection of the individual in their focus on private property rights protection, alone, respected in various forms of government, are insufficient; what matters is the security of individuals from arbitrary arrest, regardless of “type of regime”. Discretionary rights of rulers or democratic governments to arrest citizens undermines the protection of private property rights and other attributes classically given to democratic foundations of economic growth, for example, free press, freedom of the exercise of religious belief. We suggest, as a research agenda, that the power of the politically competitive system therefore comes from weakening discretionary authority over law enforcement
Keywords: P16; P50; N40; O40; 330; rule of law; Rule of Force; Personal Rights; Private Property Protection; Economic Growth